Crime in Neighborhoods: Evidence from Santiago, Chile - Olavarria-Gambi, M (Palgrave Macmillan Ltd., 2014)
On the basis of an ecological approach, this article analyzes the crime determinants in neighborhoods of Santiago, Chile. It concludes that the concentration of social disadvantages, disorder and physical deterioration, together with the presence of an oppositional subculture, is associated with a greater occurrence of crimes, and that the development of trust among the neighbors operates as a mechanism for the prevention of criminal activities. The article also identifies the implications that the relationship between crime and the characteristics of the neighborhood would have for the design of public policies aimed at preventing and controlling crime at that level. A representative survey was carried out that collected data from 5861 households belonging to neighborhoods of Greater Santiago. Data have also been collected through direct observation of the characteristics of these neighborhoods. The analyses were carried out at the micro-neighborhood (a small territorial space) and neighborhood unit (intermediate territory between the micro-neighborhood and the commune) level, and econometric estimations of count data type were applied. © 2014 Macmillan Publishers Ltd.